2012
DOI: 10.2106/jbjs.l.00072
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder Arthroscopy Simulator Performance Correlates with Resident and Shoulder Arthroscopy Experience

Abstract: This study suggests that greater resident clinical experience and shoulder arthroscopy experience are both reflected in improved performance of basic tasks on a shoulder simulator. These findings warrant further investigation to determine if training on a validated arthroscopic shoulder simulator would improve clinical arthroscopic skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 11 publications
1
45
0
Order By: Relevance
“…The generalized estimating equation (GEE) was used to complete each patient's data set based on existing values so that all patients available for 1-year or greater followup (n = 33) could be included in the analysis. The GEE is an established statistical method [1] used to deal with regression with correlated errors and nonnormal outcomes and has been used in recent orthopaedic studies [3,17]. All results are reported as means with SDs.…”
Section: Discussionmentioning
confidence: 99%
“…The generalized estimating equation (GEE) was used to complete each patient's data set based on existing values so that all patients available for 1-year or greater followup (n = 33) could be included in the analysis. The GEE is an established statistical method [1] used to deal with regression with correlated errors and nonnormal outcomes and has been used in recent orthopaedic studies [3,17]. All results are reported as means with SDs.…”
Section: Discussionmentioning
confidence: 99%
“…This simulator has been shown to correlate with timed-task arthroscopic performance in cadavers 15 and with resident and shoulder arthroscopy experience. 16 The Insight Arthro VR uses a life-size plastic shoulder with online tools that can be used on any Internet-connected computer Virtual reality simulator VR Insight Arthro VR simulator for shoulder arthroscopy Tasks Participants' performances were recorded using specific assessments on each system: The ASAT task was shape match with inverted controls. The VR tasks were operating room, locate and palpate, visualize, and pendulum.…”
Section: Vr Arthroscopic Simulator (Insight Arthro Vr)mentioning
confidence: 99%
“…However, the exact number of previous arthroscopies performed was not known. Martin et al 20 suggested that not only greater resident experience but also shoulder arthroscopy experience led to improved performance of basic tasks on a shoulder simulator. Although our study was not performed on simulators, this suggestion may hold true for live patients.…”
Section: Limitationsmentioning
confidence: 99%